2001
DOI: 10.1007/s004140000181
|View full text |Cite
|
Sign up to set email alerts
|

The detection of toxic substances in entomological specimens

Abstract: Entomotoxicology (the study of drugs in insects), a new field of forensic investigations, has still to be precisely defined especially with respect to the toxic substances that can be assessed in entomological specimens. The aim of the present work was to review the relevant entomological publications in order to analyse and describe the various toxic substances that have been detected in biological specimens. Experimental studies have been reviewed separately from case reports. Toxic substances have been clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…The toxicological analyses used for insect materials are generally the same as those used for human tissues and biological fluids Introna et al 2001;Gagliano Candela and Aventaggiato 2001) and include radioimmunoassay (RIA), gas chromatography (GC), gas chromatography/mass spectrometry (GC/MS), and highperformance liquid chromatography-mass spectrometry (HPLC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicological analyses used for insect materials are generally the same as those used for human tissues and biological fluids Introna et al 2001;Gagliano Candela and Aventaggiato 2001) and include radioimmunoassay (RIA), gas chromatography (GC), gas chromatography/mass spectrometry (GC/MS), and highperformance liquid chromatography-mass spectrometry (HPLC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…the study of drugs in insects, has become an established approach [3,4,5,6]. Whereas previously published methods have required pools of insects in order to achieve detectable levels of toxic substances [7,8,9], we have developed a LC-MS/MS method with sufficient sensitivity to allow the quantitation of benzodiazepines in single larvae or empty puparia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Various toxicological substances have been isolated from dipteran puparia [5,10,18], and their presence would provide strong evidence of origin from human remains. The absence from a pupa or puparium of toxicological substances found in the body should not, however, be used to identify it as a contaminant because it has been shown that levels of certain drugs can drop precipitously in pupariating C. vicina [19].…”
Section: Discussionmentioning
confidence: 99%